Ecocracy : Ecology Based Democracy Pursuing Local Goals of Sustainable Development in Indonesia - Retnayu Prasetyanti (Magister Ilmu Administrasi Publik, 2017)
This paper analyze the need for ecology based democracy to achieve sustainability in local development. Research results indicate that the development of democracy as it was mandated in the Green Constitution has directed the implementation of the Local Sustainable Development Goals using Ecocracy principles. The new trend of Open Local Government and Green Economy by strengthening the strategies of gender development and Ecoregion has recognized the sovereignty of the environment in local development. A qualitative CATWOE analysis concludes that in the context of local sustainable development, the ideas of Ecofeminism and Ecoregion practically take into consideration local factors which are unique and different due to the nature of diversity. Consequently, the key principle of Ecocracy must be enhanced comprehensively through enhanced participation, transparency, law enforcement, sustainability, local wisdom (socio-culture), equality (gender), accountability, efficiency and effectiveness, and welfare.